PENGEMBANGAN MEDIA BERBASIS PAPINKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS II PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Habsah, Rina; Kurnia, Ira Restu (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
To improve students' learning motivation, teachers play an important role in creating an interesting learning atmosphere. One effective media is papinka, a visual aid to understand the concept of multiplication in a concrete way, which helps improve students' motivation and understanding in learning mathematics. This study aims to develop papinka-based media to improve students' learning motivation in grade II in mathematics, especially in multiplication material. The type of research used is the type of research and development (R&D) with the ADDIE. Data collection techniques through observation, interviews, questionnaires and documentation. With a population of 25 students of grade II SDN Cipeucang 03. The data analysis technique used through quantitative and qualitative techniques. The results of the study showed that the validation results from media experts obtained an assessment with a percentage of 90%"very valid", material experts 94.4% "very valid" and language experts 92% "very valid". In addition, the assessment results obtained from the results of educator responses with a percentage of 96% "very practical or feasible", the assessment results from student responses 96.14% "very good" and the effectiveness results obtained were 96.6% "very effective". This shows that papinka media can increase student learning motivation.